Effects of task load and cognitive abilities on performance and subjective mental workload in a tracking task - Susana Rubio-Valdehita (Anales de Psicología, 2012)
The aim of this study was to determine the effects that the level of general intelligence and the aptitude profile of individuals have on performance and subjective assessments of the mental workload involved in carrying out a tracking task. Although all authors acknowledge that mental workload depends both on the characteristics of the task and the ability of individuals to perform it, little research into the real influence of these individual difference factors has been carried out. The subjects' performance and mental workload when carrying out a tracking task with different levels of difficulty were measured. Both simple effects and those relating to the interaction of the two task complexity factors were shown to have significant effects on performance and subjective mental load. Spatial aptitude was shown to have the greatest mediating effect, particularly on mental workload. Surprisingly, the subjects with the greatest ability reported higher mental workload assessments than those less able, irrespective of the instrument used to measure the workload. Finally, the subjects with greater ability achieved higher levels of performance than those less able, particularly in the more difficult tracking task.